KONTEKSTUALISASI ALQURAN: Studi atas Ayat-ayat Makkiyah dan Madaniyah melalui Pendekatan Historis dan Fenomenologis - Ali, Mohammad (Institut Agama Islam Negeri (IAIN) Palu, 2010)
The study of the compilation of the Qurâan text must begin with the character of the book itself as it was handed down by Muhammad to his companions during his lifetime. It was not delivered or, as Muslims believe, revealed all at once. It was revealed over a period of twenty-three years from the time when Muhammad began to preach in Mecca in 610 AD until his death at Medina in 632 AD. The Qurâan itself declares that Allah said to Muhammad. âWe have rehearsed it to you in slow, well-arranged stages, graduallyâ.Kata Kunci: kontekstualisasi Alquran, ayat Makkiyah, ayat Madaniyah, fenomenologi